Solution Focused Brief Counseling (SFBC): Study in Students with Academic Procrastination - Kurnanto, Muhammad Edi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
This research was motivated by preliminary research findings which show the level of academic procrastination among the students of Islamic Religious Education Department (PAI) of the Faculty of Tarbiyah and Teacher Training (FTIK) of the State Institute of Islamic Studies (IAIN) Pontianak at 71.88% which is in the high category, even at 8.75% which is in the very high class and the findings of several studies which stated that SFBC effectively overcomes various psychological problems . The research aims to prove the effectiveness of the Treatment Model of Academic Procrastination based on FSBC to reduce the behavior of academic procrastination among students who are writing their undergraduate thesis. In practice, this research used the Research and Development (R&D) approach and the model effectiveness testing, which was is conducted with One Group Pretest-Posttest Experimental Design. The data were collected using a questionnaire and analyzed using percentages and t-test. The results showed that the outcomes of the pretest-posttest average score decreased by 36.533 (from 231.666 to 195.133). Furthermore, the SFBC Model t-test showed a significance value of 0.00 (less than the alpha value of 0.05). Thus, the SFBC is sufficient to reduce the behavior of academic procrastination among the students of the Department of Islamic Religious Education (PAI) of the State Institute of Islamic Studies (IAIN) Pontianak.